Treatment of the exportation of services in the General Sales Tax: evolution and current regime - Ezeta Carpio, Sergio (2018)
The current economic relevance of international trade in services has led to the recent approval of Law No. 30641 in Peru, in order to modify several articles of the General Sales Tax Law (IGV) regarding the treatment of Export of Services. It is of importance to provide a brief review of the historical regulation of this operation in the IGV Law, which was introduced in 1982 with the already stated tax in order to later analyze the quoted Law Nº 30641 and its regulatory and complimentary rules.